Modified-Nano-Adsorbents for Nitrate Efficient Removal: A Review - Suzaimi, N. D.; Goh, P. S.; Malek, N. A. N. N. (Journal of Applied Membrane Science & Technology, 2019)
Excessive nitrate discharge into the aquatic environment from human activities is the main contributor to groundwater and surface water contamination. Its toxicity in water is a serious concern as it gives huge impacts on aquatic life since it damages the ecosystem and water sources around the globe. Recently, the development of nanomaterials as nano-adsorbent makes adsorption the most attractive solution among them. Nano-adsorbents pose high efficiency to remove pollutants from aqueous media. The exclusive chemical and structural properties of the developed nano-adsorbents are the determinative effects of nitrate adsorption performance. In this mini review, the state-of-the-art development of nano-adsorbents and nano-adsorbents-modified membranes for nitrate from water is discussed, and some challenges faced in this field are also highlighted.